Kvinnor som ett hot mot den politiska stabiliteten - Fazlhashemi, Mohammad (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
The 12th-century Persian-Islamic thinker al-Ghazâlî (1058-1111) known as a respected critic of Islamic philosophy and one of the foremost authorities of Islamic theology wrote a manual for government Nasihat al-Mulûk (Counsel for Kings) for the Turkish Saljuq sultan, Sanjar, in the mid-1090s. The Turkish tribes who had converted to Islam formed during the eleventh and twelfth centuries their own dynasties, in competition with the Caliphate in Baghdad in the eastern regions of the Islamic empire. In contrast to his earlier political writing al-Ghazâlî employed pre-Islamic Persian ideas and proclaimed the sultan to be the head of the Islamic state and elevated him to "God's shadow on earth", not once mentioning the role of the caliphate. One of the most important topics in al-Ghazâlî's manual is the issue of maintaining the political stability of the Islamic society, because it is only within a politically stable climate that society can evolve and religion be preserved. He apprehended however women's participation/interference in politics as a major threat against political stability.